Relação entre as Características Morfológicas e a Qualidade da Cortiça - Pestana, Miguel; Carneiro, Luís; Lousada, José; Sardinha, Raúl (Silva Lusitana, 2011)
. The main drive of this study was to contribute for a better knowledge about the relationship between the quality of cork and its morphology, aiming to finding out the predictive capacity of the morphological characteristics and their weight to discriminate and select cork quality. Board cork samples were taken out from 9 sample trees (3 trees x 3 sites) and they were prepared to allow quantitative classification according to punctuation classification as described by CARVALHO (1992). Data analysis was done using numerical taxonomy methods. Results generated allow emphasizing that: • The use of punctuation criteria showed the usefulness and significance of some morphological characteristics to segregate cork quality; • Good quality corks were characterized by higher values of the belly's color and low values of the belly’s relief, and its unevenness, and the size and density of the inclusions in the cork mass as well; • Bad quality corks showed a set of dominant morphological characteristics: density, distribution, aggregation and size variation of lenticels and a pronounced relief and also the size of incrustations on the belly; • The introduction of one more parameters – apparent density (DA) – in the morphological analysis did not alter quality classification
Keywords: Cork; morphology; multivariate analyses; Quality

Classificação das Cortiças para a Produção de Rolha, Recorrendo a um Critério Objectivo: Parte II - Os Provetes (Os Quadros) - Pestana, Miguel; Louzada, José; Sardinha, Raúl (Silva Lusitana, 2005)
This work intends to contribute towards better knowledge of qualitative cork qualification, through the creation of an objective classification criterion that can be reproducible, independent of the operator, and therefore be as accurate and reliable as possible. A comparison of the qualitative classification according to the punctuation criterion, applied to the cork samples of the 9 sample trees together with those generated by the criterion resulting from the data of the physical and chemical characteristics, were performed on the same cork samples striped from the same sampled trees. The results of this work emphasized that: • The objective classification based in physical and mechanical parameters assures the reproduction of the results, which does not happen with the punctuation criterion. • It was not verified that there is any relationship between the stripping positions and the quality of cork samples used. • The introduction of a chemical indicator – tenor of suberine – in the analyses of data of cork strips had not improved the segregation among the different cork qualities
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: image analyses; mechanical tests; multivariate analyses; Quality; suberine

Classificação das Cortiças para a Produção de Rolha, Recorrendo a um Critério Objectivo: Parte II - Os Provetes (Os Quadros) - Pestana, Miguel; Louzada, José; Sardinha, Raúl (Silva Lusitana, 2005)
This work intends to contribute towards better knowledge of qualitative cork qualification, through the creation of an objective classification criterion that can be reproducible, independent of the operator, and therefore be as accurate and reliable as possible. A comparison of the qualitative classification according to the punctuation criterion, applied to the cork samples of the 9 sample trees together with those generated by the criterion resulting from the data of the physical and chemical characteristics, were performed on the same cork samples striped from the same sampled trees. The results of this work emphasized that: • The objective classification based in physical and mechanical parameters assures the reproduction of the results, which does not happen with the punctuation criterion. • It was not verified that there is any relationship between the stripping positions and the quality of cork samples used. • The introduction of a chemical indicator – tenor of suberine – in the analyses of data of cork strips had not improved the segregation among the different cork qualities
Keywords: image analyses; mechanical tests; multivariate analyses; Quality; suberine